Analisis Kinerja Perusahaan dengan Menggunakan Balanced Scorecard dan Data Envelopment Analysis - Hanung Eryadi Prasetya; Bambang Subroto; Erwin Saraswati (Universitas Muhammadiyah Malang, 2017)
The objective of this research is to understand cooperation performance using integration of Balanced Scorecard and Data Envelopment Analysis an to analyze the eficiency and efectivity level by utilizing Data Envelopment Analysis based on criteria in Balanced Scorecard. The sampling determination method used non probability sampling. The research data were collected from Cooperation Agency in Jombang Regency. The data analysis instrument was performance assesment using Balanced Scorecard Perpective based on financial perspective, customer, internal bisnis, learning and growth, and also eficiency calculation using DEA output oriented model. The result of this research concludes : from financial perspective is has been there was performance improvement in 2014 and 2 Cooperation were eficient; from customer perspective it has been discovered that there was performance decline in 2014 and 2 Cooperation were eficient; from internal bisnis perspective, it has been detected that there was performance improvement in the last year and 2 Cooperation were eficient; from learning and growth perspective, it that only one Cooperation was able to reach maximum eficiency. Keywords: Performance, DEA, BSC, Efficiency